2018
DOI: 10.1038/s41598-018-32080-3
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of human milk oligosaccharides degradants within bifidobacterial communities in faecal cultures supplemented with Bifidobacterium bifidum

Abstract: Gut microbiota of breast-fed infants are generally rich in bifidobacteria. Recent studies show that infant gut-associated bifidobacteria can assimilate human milk oligosaccharides (HMOs) specifically among the gut microbes. Nonetheless, little is known about how bifidobacterial-rich communities are shaped in the gut. Interestingly, HMOs assimilation ability is not related to the dominance of each species. Bifidobacterium longum susbp. longum and Bifidobacterium breve are commonly found as the dominant species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(171 citation statements)
references
References 59 publications
11
160
0
Order By: Relevance
“…This increase was strongly promoted in the cultured sample from an infant born through Caesarean section, in which the bifidus flora was not initially confirmed (Table , Infant C). We found that promoting the growth of preexisting Bifidobacterium was difficult when only HMOs were added, but the addition of B. bifidum stimulated the formation of the bifidus flora (Gotoh et al ., ).…”
Section: Case Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…This increase was strongly promoted in the cultured sample from an infant born through Caesarean section, in which the bifidus flora was not initially confirmed (Table , Infant C). We found that promoting the growth of preexisting Bifidobacterium was difficult when only HMOs were added, but the addition of B. bifidum stimulated the formation of the bifidus flora (Gotoh et al ., ).…”
Section: Case Studiesmentioning
confidence: 97%
“…Keystone species may not always be the controlling agent at all times, but rather only under certain conditions. In the examples that we raised, the presence of an exclusive carbon source like HMOs allowed B. bifidum and LnbX + − B. longum to act as a keystone species in the bifidus flora (Yamada et al ., ; Gotoh et al ., ).…”
Section: Caveatsmentioning
confidence: 97%
See 1 more Smart Citation
“…[5,[22][23][24] Likewise, in adults, Firmicutes and Bacteroidetes are prominent in the gut, and metabolize dietary plant polysaccharides, which are otherwise indigestible by the mammalian host. Indeed, a mammalian host is unable to complete digestion of the entirety of food or to de novo produce all food-related vitamins that are critically important for a healthy living.…”
Section: Gut Microbes Are Essential For Food Digestionmentioning
confidence: 99%
“…In contrast, other bacteria can access and metabolize only specific elements of the HMO mixture. Nevertheless, microbial communities may be capable to act in concert, consecutively breakdown and metabolize HMO structures in a team effort through cross-feeding activities (Egan et al, 2014a,b;Gotoh et al, 2018).…”
Section: The Origin Of the Human Gut Microbiotamentioning
confidence: 99%